THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING APPROACH AND LEARNING MOTIVATION TOWARD WRITING SKILLS OF PANTUN IN THE FIFTH GRADE STUDENTS OF ELEMENTARY SCHOOL - Resti Adna Helda; Mardiah Harun (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study was conducted to observe the effect of the Contextual teaching and learning (CTL) approach and learning motivation on the skills of writing Pantun of fifth graders in elementary school. This research was an experimental research with the subject of fifth grade students and carried out in Elementary School Cluster I Pariaman City. The research instruments were a learning motivation questionnaire and performance test. Data analysis was carried out using a two-way ANAVA and t-test. Learning outcomes obtained by using the CTL approach to students was higher than conventional methods, both low motivation and high motivation. CTL approach makes students more interested and enthusiastic in learning to write Pantun. As well as creating new experiences for students, it makes students active and learning more fun compared to conventional methods which make some students become passive.